Factors Influencing the Success of E-prescribing in Hospitals: A Literature Review - Nadia Miftahul Aini; Rasmi Zakiah Oktarlina; Selvi Marcellia; Syazili Mustofa (SEAN Institute, 2026)
Electronic prescribing (e-prescribing) is an information technology–based innovation in healthcare systems aimed at improving patient safety and quality of care, particularly in the medication prescribing process. The implementation of e-prescribing in hospitals has been shown to reduce medication errors; However, its success is influenced by various complex and multidimensional factors. This study aims to identify and analyze the factors affecting the successful implementation of e-prescribing in hospitals using a literature review approach. The results indicate that the success of e-prescribing implementation is influenced by individual factors (knowledge, attitudes, and user skills), technological factors (system quality, user interface design, and clinical decision support systems), organizational factors (management support, infrastructure readiness, and workflow), and policy factors (regulations and interoperability standards). Additionally, several barriers were identified, including limited infrastructure, user resistance, alert fatigue, and technology-induced errors that may affect system effectiveness. Therefore, a comprehensive and integrated approach is required to optimize the implementation of e-prescribing in improving patient safety and healthcare service quality in hospitals.